Mastocytosis with clinical features of histyocitosis. - Betto, P.; Gennari, E.; Cambiaghi, S.; Niccoli, A. (European Journal of Pediatric Dermatology, 2006)
Cutaneous mastocytosis is a rare disorder characterized by an increased number of mastocytes in the dermis. Pseudoxanthomatous mastocytosis is a rare clinical variant reported by Fox in 1883, clinically characterized by yellowish and brownish papules and nodules, wich are reminiscent of xanthoma or histiocytosis. The Darier sign is slightly positive.